Sistem Penunjang Keputusan Pemilihan Mekanik Terbaik Menggunakan Metode Weighted Product pada PT. Paramita Banindo - Khaerul Ma'mur; Bagas Maulina (Journal of Artificial Intelligence and Innovative Applications (JOAIIA), 2020)
One of the determinants of customer satisfaction is that employees can serve customers and finish their work well. Therefore, PT. Paramita Banindo Perform the best mechanical selection in every month to improve the mechanic's performance and can serve the customers with the best serving. The process of screening used conventional ways and subjective ways to avoid injustice. Therefore, the calculation of the method of Weighted Product (WP) that is considered can result in precise calculation of the selection of the best mechanics. The Data obtained is also more actual and accurate than the previous system that requires entry more than once when there is a change. Weighted Product method is chosen because the calculation process is not so complex, so it is suitable applied to this decision support system. With the application of Weighted Product method, the resulting system becomes integrated so as to facilitate data collection and documentation.